Environmental health: a critical review of the impact of climate change, COVID-19, and other emerging threats - Linda Qiu; Lu Liu; M. Santosh (Discover Sustainability)
Abstract With the increasing frequency of extreme weather changes and emerging threats, environmental health is of great concern. Based on existing studies, the interaction among environmental health, climate change, COVID-19, and human health is obvious and complex. Depending on a systematic analysis of academic databases, such as PubMed, Web of Science, MedRxiv, and many top journals in the field, this study evaluates the topics of environmental health and climate change generally and analyzes and compares the key investigations on related topics. This systematic and critical review has attempted to explain environmental health from multiple influencing factors, especially climate change and the COVID-19 pandemic, which might be essential to future studies in these fields. As a review piece of work, this study explores some key issues that have been examined by scholars in the related fields and provides a holistic framework that can be used in many aspects of the issues.